2008
DOI: 10.1007/s10433-008-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Home help services in Sweden: responsiveness to changing demographics and needs

Abstract: Decreases in Swedish home help services have not resulted in increased rates of unmet need. To understand these changes, we identified predictors of home help services and rates of institutional care and how these effects changed over time using longitudinal data (1994-2000) from 286 Swedish municipalities. Outcomes were home help coverage rates, intensity of home help per recipient, and rates of institutional living. Predictors reflected availability and need for services. Services decreased over time, but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 24 publications
(26 reference statements)
1
26
0
1
Order By: Relevance
“…Several studies focused on the relationship between formal home care provision and informal care [28,29,32,34,38,39,42,44,46,51,54,57,58,64,69,73,75,79-81]. Quality and improvement of quality were the subject of seven studies [10,28,49,54,68-70].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies focused on the relationship between formal home care provision and informal care [28,29,32,34,38,39,42,44,46,51,54,57,58,64,69,73,75,79-81]. Quality and improvement of quality were the subject of seven studies [10,28,49,54,68-70].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have suggested that there are advantages to decentralization, assuring that the differences in degrees of coverage and intensity of services should be viewed as an achievement in the state's ability to offer responses to regional differences in population needs. Jyoti Savla et al (2008), for example, in an attempt to determine the factors affecting the existence of differing levels of home care services in Swedish municipalities, found empirical evidence that such differences were based on distinct municipal needs. In this way, the widest access to care services was provided in those areas having the highest percentage of elderly.…”
Section: Territorialization Of Formal Service Provision and Its Influmentioning
confidence: 99%
“…Algunos autores han señalado las ventajas de la descentralización, asegurando que las diferencias en los grados de cobertura e intensidades en los servicios de provisión de cuidados deben ser apreciadas como un éxito de los Estados para dar respuesta a la desigualdad espacial de las necesidades de la población. Jyoti Savla et al (2008), por ejemplo, en un intento de averiguar los factores que afectan a la existencia de niveles muy dispares en los servicios de ayuda a domicilio entre los municipios suecos, han encontrado evidencias empíricas de que dichas diferencias obedecen a distintas exigencias a escala municipal. De esta forma, el acceso más amplio a los servicios de cuidados se da en aquellos territorios donde el porcentaje de adultos mayores es más elevado.…”
unclassified
“…Large variations in availability of services were noted during the 1990s (56), and since 1993 the national government has provided grants to municipalities to adjust for differences in income tax bases, costs of providing care, and demographic factors beyond the control of municipalities (33). More recently, researchers have concluded that variations in levels of home-and community-based services for the elderly are highly correlated with differences in levels of need among municipalities rather than with differences in financial resources or decisions by municipal agencies regarding eligibility (23,48). A different interpretation of the past decade's smaller variations in spending by municipality is that the national government has stressed the need for systematic assessments of elderly applicants to ensure fairness in decisions about services to be provided (56).…”
Section: What Level Of Government Determines Need and Organization Ofmentioning
confidence: 99%